Biological relevance of computationally predicted pathogenicity of noncoding variants - Li Liu (Nature Portfolio, 2019)
Researchers can make use of a variety of computational tools to prioritize genetic variants and predict their pathogenicity. Here, the authors evaluate the performance of six of these tools in three typical biological tasks and find generally low concordance of predictions and experimental confirmation.